Pengembangan Peta Percepatan Gerakan Tanah Puncak Kota Semarang Berdasarkan Peraturan Gempa Tahun 2019 - Partono, Windu; Irsyam, Masyhur; Nazir, Ramli; Asrurifak, Muhammad; Kistiani, Frida; Sari, Undayani Cita (MEDIA KOMUNIKASI TEKNIK SIPIL, 2021)
Surface peak ground acceleration (PGAM) needs for seismic forces of basement and retaining structures design.  The PGAM value can be calculated using bedrock peak ground acceleration (MCEG) and multiplied it with site coefficient FPGA. For building design purposes, the MCEG value can be calculated based on the combination of DSHA (Deterministic Seismic Hazard Analysis) and PSHA (Probabilistic Seismic Hazard Analysis). Compared to the previous 2012 website response spectrum design which is displayed the PGAM value, only MCEG value at site position can be obtained from the new 2021 response spectrum design website. This paper describes the development of PGAM distribution of Semarang using Visual Basic programming language software. The distribution of DSHA and PSHA (2500 return periods) combination analysis for developing MCEG value also describes in this paper. The analysis was performed based on the earthquake record data from 1900 to 2016. The PGAM analysis was performed at 203 soil boring investigation positions and using FPGA site coefficients of SNI 1726:2019. The minimum and maximum PGAM distribution values at the study area are in between 0.45 through 0.55 g and the maximum PGAM is distributed at the northern part of the study area.